Estudo em laboratório de anomalias de potencial espontâneo - FERREIRA, Lindalva do Carmo (Universidade Federal do Pará, 2014)
This work is an application in the laboratory of the Spontaneous or Self Potential method of field geophysics. Pairs of differente rocks and residual soils were placed in contact in the laboratory to determine whether they could produce a difference in potential, as had been occasionally observed during field investigations. The samples of rock used are limestones, basalts, and rhyolite from the area of "Caldera de Los Humeros" in Mexico. The residual soils are from the area MM1 of "Serra dos Carajás", Pará, Brasil. The measurements were carried out using dry systems (room humidity) and humid systems (water added). The changes of measured potential for rocks and soils in the laboratory show differences in average values ranging from 5mv to 50 mv from one side of a contact to the other. Thus, the result of this investigation in positive and indicates that changes in Self Potential values can originate from changes in superficial soil type or by contacts between different types of rocks.